Automatic processing of macromolecular crystallography X‐ray diffraction data at the ESRF. (15th May 2013) - Monaco, Stéphanie; Gordon, Elspeth; Bowler, Matthew W.; Delagenière, Solange; Guijarro, Matias; Spruce, Darren; Svensson, Olof; McSweeney, Sean M.; McCarthy, Andrew A.; Leonard, Gordon; Nanao, Max H.
Abstract : The development of automated high‐intensity macromolecular crystallography (MX) beamlines at synchrotron facilities has resulted in a remarkable increase in sample throughput. Developments in X‐ray detector technology now mean that complete X‐ray diffraction datasets can be collected in less than one minute. Such high‐speed collection, and the volumes of data that it produces, often make it difficult for even the most experienced users to cope with the deluge. However, the careful reduction of data during experimental sessions is often necessary for the success of a particular project or as an aid in decision making for subsequent experiments. Automated data reduction pipelines provide a fast and reliable alternative to user‐initiated processing at the beamline. In order to provide such a pipeline for the MX user community of the European Synchrotron Radiation Facility (ESRF), a system for the rapid automatic processing of MX diffraction data from single and multiple positions on a single or multiple crystals has been developed. Standard integration and data analysis programs have been incorporated into the ESRF data collection, storage and computing environment, with the final results stored and displayed in an intuitive manner in the ISPyB (information system for protein crystallography beamlines) database, from which they are also available for download. In some cases, experimental phase information can be automatically determined from the processed data. Here, the system is described in detail.